PERANAN UANG DALAM PERSPEKTIF SYARIAH ISLAM - Eni Kusrini (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2019)
The role of money is very important in human life. Without money, economic sector will not play the role and functioning as it should. Moreover, the modern economy, the trading bank system plays a role in determining circulation of the amount of money. so as to be able to influence money above the level of the State's economic activity. For a long time economists realized that money could have good and bad effects on the existing economy. Excessive offers cause inflation.However, in times of high unemployment, the addition of money can be a stimulant in accelerating economic growth. At this time economists agree that the money available in the economy is very influential in determining stability and economic growth. Furthermore, the existence of the money function is regulated by the government’s policies. In addition, there are also various banks that are used as a forum for the public to support the circulation of money in the State.